Effective removal of Cr(VI) from aqueous solution by iron‐carbonized solid waste composite: behavior mechanism and factor analysis. Issue 4 (28th October 2022) - Shi, Yahui; Zhang, Hongkui; Wei, Yawei; Wan, Dongjin; Liu, Yongde; Gao, Yafei
Abstract: BACKGROUND: The spent bleaching earth (SBE) is a solid waste produced during the refining of vegetable oil, with features of high residual oil and difficult disposal. At present, pollution control by the treatment of waste is a hot issue to attract more and more attention. This study used SBE as the raw materials and developed a new type of iron‐carbon composite (Fe x O y /SBE@C) by loading iron on spent bleaching earth carbon (SBE@C) to remove Cr(VI) in water. SBE@C was obtained by the pyrolysis of SBE. RESULTS: The behavior mechanism and factor analysis of Fe x O y /SBE@C for Cr(VI) removal in water were investigated for the first time. At first, one‐factor experiments in the preparation process were adopted to obtain Fe x O y /SBE@C with optimal performance. By characterization analysis of the optimal Fe x O y /SBE@C before and after Cr(VI) removal, it was found that the Cr(VI) removal mechanism was adsorption followed by reduction. Specifically, the adsorption kinetic and isotherm behaviors of Fe x O y /SBE@C for Cr(VI) belong to the pseudo‐second‐order kinetic model and Langmuir isotherm, respectively. Cr(VI) removal by Fe x O y /SBE@C is spontaneous (△ G <0) and endothermic (△ H >0). The presence of coexisting anions (i.e., BrO3 − < SO4 2− < PO4 3− ) and the increase of pH (only adsorption at pH>7) are not conductive to Cr(VI) removal by Fe x O y /SBE@C. Fortunately, N2 atmospheres can promote Cr(VI) removal ( 100%) that is significantly higher than those in air atmosphere (63.34%) and natural conditions (82.25%). CONCLUSION: Overall, Fe x O y /SBE@C has the satisfactory Cr(VI) removal performance through physical adsorption and chemical reduction, and exhibits great potential application value in Cr(VI) elimination from water. © 2022 Society of Chemical Industry.